СРАВНИТЕЛЬНЫЙ АНАЛИЗ НЕПРИЛИВНЫХ ВАРИАЦИЙ ВЕРТИКАЛЬНОГО ГРАДИЕНТА СИЛЫ ТЯЖЕСТИ В ПУНКТАХ НАБЛЮДЕНИЯ С РАЗЛИЧНОЙ ГЕОГРАФИЧЕСКОЙ ШИРОТОЙ - Антонов Ю.В.; Жаворонкин В.И.; Слюсарев С.В. (My University, 2003)
In article results of measurements not-tidal variations of vertical gradient of gravity are considered in the cities of Voronezhs, Apatites, Velsk. On periodograms the general periods are marked by duration of 44 and 29 minutes.
Keywords: 550.831